Efektivitas Penerapan Model Discovery Learning Terhadap Hasil Belajar Fiqih Siswa Kelas VIII Di MTSN 1 Kota Payakumbuh - Arisa Maisyarah; Nurhasnah Nurhasnah; Alimir Alimir; Hamdi Abdul Karim (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This research was conducted at MTsN 1 Kota Payakumbuh based on several problems that the author found in class VIII MTsN 1 Kota Payakumbuh. This study was motivated by the lack of variety in the learning model applied in class, so that students were less active and felt bored in participating in the learning process, learning outcomes were less than optimal, and did not match what was expected. This research aims to find out how fiqh learning is implemented using the discovery learning model and the effectiveness of implementing the discovery learning model on the fiqh learning outcomes of class VIII students at MTsN 1 Kota Payakumbuh. This research is quantitative experimental research using a quasi-experimental approach. This research is located at MTsN 1 Kota Payakumbuh. The sample in this study consisted of two classes, namely the control class and the experimental class, with sampling using random sampling techniques. The instruments used in this research were observation, learning outcomes tests, and documentation. Based on research results from the N-Gain Score test results, it can be seen that the average score for the experimental class using the discovery learning model is 63.3982 or 63%, which is in the quite effective category. Meanwhile, for the control class whose learning was through lectures, an average of 24.0655 or 24% was obtained, which was included in the ineffective category. This means that there are significant differences in student learning outcomes between classes that use the discovery learning model and classes that do not use the discovery learning model. So, it can be concluded that there is effectiveness in applying the discovery learning model to the Fiqh learning outcomes of Class VIII students at MTsN 1 Kota Payakumbuh.